Peningkatan Kesadaran Global Siswa IPA Sebagai Dasar Pendidikan Masa Depan - Mulia Rasyidi; Muhammad Sarjan; Agus Muliadi; Asrorul Azizi; Hamidi Hamidi; Iswari Fauzi; Muhammad Yamin; Muh. Zaini Hasanul Muttaqin; Bakhtiar Ardiansyah; Rindu Rahmatiah; Sudirman Sudirman; Yusran Khery (Peneliti.net, 2022)
The skills of students in the global era or the twenty-first century become a very important topic in learning. The lack of students' understanding of 21st century skills is caused by a lack of global awareness and the importance of global skills which are the basis for developing students' self as citizens of the world. Globalization shows that the world is getting smaller, the dependence between nations is getting bigger. Globalization is a globalizing process, meaning that all activities are calculated for the benefit of the world. Therefore, it is necessary to study in-depth literature on increasing global awareness as the basis for future education. The method used is literature review. The source of the literature review used is in the form of articles that are in accordance with this article. students need academic and applied knowledge, can connect knowledge and skills, be creative and adaptive, and be able to transform all these aspects into valuable skills. Students must have skills that include: (1) Critical Thinking Skills; (2) Problem Solving Ability; (3) Communication and Collaboration; (4) Creativity and Innovation; (5) Information, Communication, and Technology Media Literacy